ENHANCING ENGLISH SPEAKING SKILLS THROUGH BLENDED LEARNING: A STUDY ON JUNIOR HIGH SCHOOL - Elpi Ulan Tiara (Universitas Samudra, 2025)
This study aims to know the effect and to describe students’ responses to the Blended learning method in improving student English language learning affects students' speaking skills at SMP Negeri 5 Langsa. This research uses a quantitative experimental method with a one-group pre-test and post-test design. The research sample consists of one ninth-grade class with 28 students, selected using purposive sampling. Data collection was conducted using a speaking test and a questionnaire to determine students’ responses to the use of the blended learning method. Data analysis was carried out using a t-test. The results indicate an improvement in students’ speaking ability, as evidenced by a significant increase in students' pre-test and post-test scores. The average student score increased from 38.57 (pre-test) to 75.46 (post-test). Based on statistical analysis, the t-test results were compared with the t-table values at both a 5% significance level (2.052) and a 1% significance level (2.771). The results showed that at both significance levels, the observed t-value was higher than the t-table value. Furthermore, the questionnaire results also indicated that English learning using the blended learning method received positive responses from students. Thus, The results of this study show that the use of blended learning methods affects students' Speaking skill.